Structural trends in atomic nuclei from laser spectroscopy of tin - Yordanov, Deyan T.; Rodríguez, Liss V.; Balabanski, Dimiter L.; Bieroń, Jacek; Bissell, Mark L.; Blaum, Klaus; Cheal, Bradley; Ekman, Jörgen; Gaigalas, Gediminas; Garcia Ruiz, Ronald F.; Georgiev, Georgi; Gins, Wouter; et al. (Communications Physics, 2020)
Tin is the chemical element with the largest number of stable isotopes. Its complete proton shell, comparable with the closed electron shells in the chemically inert noble gases, is not a mere precursor to extended stability; since the protons carry the nuclear charge, their spatial arrangement also drives the nuclear electromagnetism. We report high-precision measurements of the electromagnetic moments and isomeric differences in charge radii between the lowest 1/2+, 3/2+, and 11/2− states in 117–131Sn, obtained by collinear laser spectroscopy. Supported by state-of-the-art atomic-structure calculations, the data accurately show a considerable attenuation of the quadrupole moments in the closed-shell tin isotopes relative to those of cadmium, with two protons less. Linear and quadratic mass-dependent trends are observed. While microscopic density functional theory explains the global behaviour of the measured quantities, interpretation of the local patterns demands higher-fidelity modelling.
CRIS-Team Scopus Importer:2020-06-16